Risk Elements Linked to Oral Candidiasis (Medicine Today, 2025)
Introduction: Oral candidiasis is also called oral thrush or oropharyngeal candidiasis. In this condition, the fungus named Candida albicans (C. albicans) accumulates on the lining of the oral cavity. The typical colonization rate of C. albicans varies with age. In neonates it is around 45%; in healthy children ranging between 45–65%; in healthy adults about 30–45%. Objectives: This study aimed to find out the risk factors, and symptoms and identify the different types of clinical presentations according to the classifications, as well as trace out the drugs which is commonly being used. Materials and Methods: This prospective observational study was conducted at the Shishu Hospital, Shaymoly, Dhaka, and Rajshahi Medical College (RMC), Rajshahi with the ethical clearance of the review board, between January 2016 and December 2016. In this study, 386 patients were enrolled out of which 286 patients were from Shishu Hospital, Shamoly, Dhaka and 100 were from RMC who had the positive clinical features of Candida infection. Results: Out of the 247(64%) patients had dry mouth. About 62(16%) patients had dental prostheses, such as dentures or fillings. Around 42(11%) patients were using steroid drugs. Almost 259(67%) patients gave a history of unhealthy dietary intake. The systemic factor was that more than 235(61%) patients in our study were belonging two adverse age groups. About 239(62%) patients had malnutrition. Around 127(33%) patients had a history of using long-term antibiotics. In our study 142(37%) patients had a history of Diabetes Mellitus. In the case of 335(87%) cases creamy white lesions on the surface of the tongue. Loss of taste sensation had to 127(33%) cases. Conclusion: In the last few decades, a huge amount of clinical data has been recorded on oral candidiasis to its advent with various immunocompromised conditions. With the development of antifungal drugs, this disease has been controlled better than the previous decades.Medicine Today 2025, Vol.37 (1): 93-98